Graphitized carbon loaded platinum-based catalyst and preparation method thereof
Through ultra -fast heating treatment and impregnating legal preparation of graphite carbonized platinum -based catalysts, the problem of less existing graphite carbon carbon carrier has less abity. Sex and corrosion resistance.
Patent Information
- Application Number
- CN202411583772.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-28
AI Technical Summary
The specific surface area of the existing graphitized carbon supports is small and there are few defect sites, resulting in poor dispersion and degradation of the platinum-based catalyst.
Treatment of non -graphitized solid carbon materials through ultra -fast heating, improve graphite, and load platinum -based nanoparticles on graphite carbonized materials by impregnating method to prepare high -activated and high -stabilized graphite carbon -based platinum base catalysts loaded Essence
It improves the surface area and defect site of graphitized carbon materials, enhances the decentralization and stability of the platinum -based catalyst, and improves the activity and corrosion resistance of catalysts.
Smart Images

Figure CN119381468A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell technology, and mainly to a graphitized carbon-supported platinum-based catalyst and a preparation method thereof. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC) is an efficient energy conversion device that can directly convert the chemical energy stored in hydrogen fuel and oxidant into electrical energy through electrochemical reactions. It has the characteristics of green environmental protection, high specific energy, low temperature rapid start and high stable operation. It is considered to be an ideal power source to replace internal combustion engines. However, the current application of PEMFC still has some limitations, mainly reflected in the high catalyst cost, insufficient power density and poor durability. Therefore, in order to achieve large-scale application of proton exchange membrane fuel cells, solving the above problems is crucial for the development of advanced catalysts. Among them, the interaction between catalyst support materials and catalyst particles is one of the main focuses of catalyst research. Support materials are crucial for regulating the properties of platinum nanoparticles (Pt NPs) (such as dispersion, shape, size and structure), and to a certain extent determine the performance of catalysts. Catalyst supports are usually composed of carbon materials. In addition to providing electronic conduction, their surface defects and other locations can also become anchor points for platinum or platinum-based alloy catalyst particles to anchor. At present, ordinary carbon materials have a high specific surface area and more defect sites, and they are better combined with catalysts, but have low stability. Carbon materials with a higher graphite structure have excellent corrosion resistance, but the higher the degree of graphitization, the fewer defect sites there are for the catalyst material to bind to, and their poor dispersibility will lead to a decrease in catalyst performance. In addition, carbon carriers with a high degree of graphitization usually have a lower Brunauer-Emmett-Teller (BET) specific surface area, which causes the catalyst particles to be more closely aggregated together, thereby promoting the speed of particle agglomeration and accompanied by a faster loss of ECSA. Therefore, the insufficient loading performance of existing carbon material carriers limits the performance of platinum-based catalysts, and the existing technology needs to be improved and developed. Summary of the invention
[0003] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a graphitized carbon-supported platinum-based catalyst and a preparation method thereof, aiming to solve the problem of small specific surface area and few defect sites on the existing graphitized carbon carrier.
[0004] The technical solution of this application is as follows: In a first aspect, the present application provides a method for preparing a graphitized carbon-supported platinum-based catalyst, which comprises the following steps: The non-graphitized solid carbon material is subjected to ultra-fast heating treatment for graphitization to obtain a graphitized solid carbon material; Loading platinum-based nanoparticles on the graphitized solid carbon material by an impregnation method to obtain the graphitized carbon-loaded platinum-based catalyst; The ultrafast heating treatment is carried out under the conditions of 1200-3000° C. for 0.05-500 s.
[0005] The present application can improve the degree of graphitization by ultrafast heating, and the graphitization degree of the obtained graphitized solid carbon material is greater than 10%, retains a large number of lattice defect sites and has a high specific surface area. The graphitized solid carbon material has high corrosion resistance and can provide a large number of defect sites for platinum and platinum-based alloy nanoparticles to be uniformly loaded, thereby obtaining a highly active and highly stable graphitized carbon-loaded platinum-based catalyst.
[0006] Furthermore, the step of loading platinum-based nanoparticles on the graphitized solid carbon material by impregnation method comprises: The platinum-containing precursor solution, deionized water and the graphitized solid carbon material are prepared into a slurry with a platinum-based nanoparticle loading of 1-80 wt %, and dried to obtain a mixture; The mixture was transferred to a quartz boat and placed in a tube furnace, annealed in a reducing inert mixed atmosphere, taken out after cooling and dispersed in a 0.5 mol / L sulfuric acid solution, and magnetically stirred for 1-2 hours to obtain a mixed solution at a stirring speed of 200-600 rpm; The mixed solution was filtered and washed with deionized water, and dried at 70-100° C. overnight under vacuum conditions.
[0007] Furthermore, the annealing temperature is 300-600°C and the annealing time is 0.1-10h. In the present application, the carbon material is subjected to ultrafast heating treatment, and the annealing temperature will affect the performance of the prepared catalyst. By controlling the treatment at a suitable high temperature, the surface of the carbon material can be changed, the active center of the catalyst can be rearranged, and the morphology can be transformed, thereby enhancing the activity and stability.
[0008] Further, the platinum-based nanoparticles are one of platinum nanoparticles or platinum-based alloy nanoparticles, the platinum-based alloy nanoparticles are alloy nanoparticles of platinum and metal M, and the metal M is one or more of gold, cobalt, nickel, iron or ruthenium; The platinum-containing precursor solution is a platinum precursor solution, or the platinum-containing precursor solution includes a platinum precursor solution and a metal M precursor solution, and the content of the metal M accounts for 1-50% of the total metal atoms.
[0009] Furthermore, the platinum precursor is one or more of H2PtCl6∙6H2O, K2PtCl6, Na2PtCl6, Na2PtCl4, K2PtCl4, Pt(NH3)4Cl2, Pt(NH3)2(NO2)2, and Pt(NO3)2.
[0010] Furthermore, the metal M precursor is one or more of chloroauric acid, cobalt chloride, cobalt nitrate, cobalt sulfate, cobalt acetate, cobalt acetylacetonate, nickel nitrate, ruthenium chloride, ferric chloride, and ferric nitrate.
[0011] Furthermore, the platinum-based nanoparticle loading is 5-60wt%.
[0012] Furthermore, the reducing inert mixed atmosphere is an argon-hydrogen mixed atmosphere, and the hydrogen content in the argon-hydrogen mixed atmosphere is 1-20%.
[0013] Furthermore, the non-graphitized solid carbon material is one or more of Vulcan XC72, KB300, KB600, BP2000, and Toray carbon.
[0014] In a second aspect, the present application further provides a graphitized carbon-supported platinum-based catalyst, wherein the catalyst is prepared by the preparation method of the graphitized carbon-supported platinum-based catalyst as described in the first aspect.
[0015] Beneficial effects: The preparation method of the present application is simple and efficient. The preparation method can prepare a platinum-based catalyst supported by graphitized carbon with multiple defects, which can be used for the catalytic oxygen reduction reaction of PEMFC. This catalyst has high corrosion resistance, uniform particle distribution size, high specific surface area, and higher performance and stability than commercial platinum-carbon catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 TEM images of the initial carbon material (a) and the graphitized carbon material (b) after ultrafast heating treatment in Example 1 of the present application.
[0017] Figure 2 This is the BET diagram of the graphitized carbon material subjected to ultrafast heating treatment in Example 1 of the present application.
[0018] Figure 3 This is the Raman graph of the graphitized carbon material subjected to ultrafast heating treatment in Example 1 of the present application.
[0019] Figure 4 1 is the XRD diagram of each platinum-based catalyst in Examples 1-4 of the present application.
[0020] Figure 5 This is the TEM image of the platinum-based catalyst in Example 1 of the present application.
[0021] Figure 6 TEM image of platinum-based catalyst for graphitized carbon obtained by conventional heating.
[0022] Figure 7 This is the TEM image of the platinum-based catalyst in Example 2 of the present application.
[0023] Figure 8 This is the TEM image of the platinum-based catalyst in Example 3 of the present application.
[0024] Fig. 9 This is the TEM image of the platinum-based catalyst in Example 4 of the present application.
[0025] Fig.10 It is a comparison chart of the activity test polarization curves of each platinum-based catalyst in Examples 1-4 of the present application and the comparative example.
[0026] Fig.11 This is a test chart of the cyclic stability of the platinum-based catalyst in Example 2 of the present application.
[0027] Fig.12 This is a bar graph of activity decay in the stability test of the platinum-based catalyst in Example 2 of the present application. DETAILED DESCRIPTION
[0028] The present application provides a graphitized carbon-supported platinum-based catalyst and a preparation method thereof. To make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0029] At present, ordinary carbon materials have a high specific surface area and more defects, and they combine well with platinum-based catalysts, but they have low stability and are easily corroded under working conditions, which directly affects the stability of the catalyst. Catalysts supported by highly graphitized carbon carriers have excellent corrosion resistance, but due to their low specific surface area and defects, they cannot provide more sites for the anchoring of platinum-based nanoparticles, and the catalysts cannot be effectively dispersed and loaded on highly graphitized carriers.
[0030] To address this problem, the present application provides a method for preparing a graphitized carbon-supported platinum-based catalyst, which comprises the following steps: The non-graphitized solid carbon material is subjected to ultra-fast heating treatment for graphitization to obtain a graphitized solid carbon material; Platinum-based nanoparticles are loaded on graphitized solid carbon materials by an impregnation method to obtain a graphitized carbon-loaded platinum-based catalyst.
[0031] The preparation method provided in the present application can produce a graphitized solid carbon material with a high degree of graphitization, a large number of lattice defect sites and a high specific surface area. The graphitized solid carbon material has high corrosion resistance and can provide a large number of defect sites for uniform loading of platinum and platinum-based alloy nanoparticles, thereby producing a graphitized carbon-loaded platinum-based catalyst with high activity and high stability.
[0032] Specifically, amorphous carbon generally undergoes atomic rearrangement at high temperatures, rearranging from the originally disordered amorphous state into a layered hexacyclic graphite crystal structure at temperatures above 2000°C. This process is usually completed at high temperatures for a long time. However, graphitized materials heated for a long time are not suitable as catalyst carriers for the following reasons: (1) The surface is smooth with few defects and has no anchoring effect, so the catalyst is prone to agglomeration; (2) The specific surface area is small and is not suitable for catalyst dispersion.
[0033] Further, the condition of ultrafast heating treatment is ultrafast heating treatment at 1200-3000 ° C for 0.05-500s, preferably 0.05-50s. In the present application, it is not necessary to add a catalyst, and the non-graphitized carbon is subjected to high-temperature treatment by ultrafast heating to impart energy, so that its structure changes and is transformed into an ordered graphitized carbon with a van der Waals interlayer structure. At the same time, ultrafast heating occurs in seconds or even milliseconds, and atoms do not have time to complete effective rearrangement, and a lot of defect sites will be generated on the surface, realizing partial structural graphitization. The graphitized structure is evenly distributed, and the surface of the carbon material is interspersed with partial graphitized structures and partial non-graphitized structures, so that the properties of the carbon material are more stable, and the electrical conductivity, thermal conductivity and corrosion resistance are improved. It has a high specific surface area while having a high degree of graphitization, and has many defect sites for catalyst materials to combine, reducing the agglomeration of particles, and the loaded catalyst has good activity and durability.
[0034] Further, the step of loading platinum-based nanoparticles on the graphitized solid carbon material by an impregnation method comprises: A platinum-containing precursor solution, deionized water and a graphitized solid carbon material are prepared into a slurry with a platinum-based nanoparticle loading of 1-80 wt%, and a mixture is obtained after drying; The mixture was transferred to a quartz boat and placed in a tube furnace, annealed in a reducing inert mixed atmosphere, taken out after cooling and dispersed in a 0.5 mol / L sulfuric acid solution, and magnetically stirred for 1-2 hours to obtain a mixed solution at a stirring speed of 200-600 rpm; The mixed solution was filtered and washed with deionized water, and dried at 70-100° C. overnight under vacuum conditions.
[0035] The graphitized carbon obtained by the treatment of the present application can effectively reduce the degree of agglomeration when preparing a catalyst by an impregnation method.
[0036] Furthermore, the annealing temperature is 300-600°C, and the annealing time is 0.1-10h, preferably 1h. In the present application, the carbon material is subjected to ultrafast heating treatment, and the annealing temperature will affect the performance of the obtained catalyst. By controlling the annealing treatment at a suitable high temperature, the surface can be changed, the active center of the catalyst is rearranged, and the morphology is transformed, thereby enhancing the activity and stability. Among them, if the annealing temperature is too high, it will cause the particles to agglomerate and the performance will be reduced. If the annealing temperature is too low, the particle size of metal nanoparticles such as Pt will be too small. Too small platinum nanoparticles show high surface energy and are easy to dissolve rapidly in an electrochemical environment, thereby accelerating the degradation of the catalyst.
[0037] Further, the platinum-based nanoparticles are one of platinum nanoparticles or platinum-based alloy nanoparticles, the platinum-based alloy nanoparticles are alloy nanoparticles of platinum and metal M, and the metal M is one or more of gold (Au), cobalt (Co), nickel (Ni), iron (Fe) or ruthenium (Ru); the platinum-containing precursor solution is a platinum precursor solution, or the platinum-containing precursor solution includes a platinum precursor solution and a metal M precursor solution, and the content of metal M accounts for 1-50% of the total metal atoms. In the present application, by introducing a second element into the platinum-based catalyst, the activity and stability indicators are greatly increased, and it has the advantage of low production cost.
[0038] The platinum precursor is one or more of H2PtCl6∙6H2O, K2PtCl6, Na2PtCl6, Na2PtCl4, K2PtCl4, Pt(NH3)4Cl2, Pt(NH3)2(NO2)2, and Pt(NO3)2, preferably H2PtCl6∙6H2O. The metal M precursor is one or more of chloroauric acid, cobalt chloride, cobalt nitrate, cobalt sulfate, cobalt acetate, cobalt acetylacetonate, nickel nitrate, ruthenium chloride, ferric chloride, and ferric nitrate.
[0039] Furthermore, the loading amount of the platinum-based nanoparticles is 5-60 wt %, preferably, the loading amount is the commonly used 40 wt % loading amount.
[0040] Furthermore, the reducing inert mixed atmosphere may be an argon-hydrogen mixed atmosphere with a hydrogen content of 1-20%. The catalyst is protected from burning at high temperatures by the inert gas, and platinum is reduced by the reducing gas reaction.
[0041] Furthermore, the non-graphitized solid carbon material is one or more of carbon materials with a low degree of graphitization such as Vulcan XC72, KB300 (Ketjen Black 300), KB600 (Ketjen Black 600), BP2000, Toray carbon and amorphous carbon. Preferably, the non-graphitized solid carbon material is preferably KB600, which has a better load effect after ultrafast heating.
[0042] The preparation method provided in the present application is simple and efficient, and can be easily adjusted for large-scale preparation. By means of the preparation method, a graphitized carbon-loaded material with a high degree of graphitization, a high specific surface area and many defect sites can be prepared, and then a graphitized carbon-loaded platinum-based catalyst with high activity and high stability can be prepared.
[0043] The present application also provides a graphitized carbon-supported platinum-based catalyst, wherein the catalyst is prepared by the preparation method of the graphitized carbon-supported platinum-based catalyst as described above. The present application develops a multi-defect graphitized carbon carrier-supported platinum-based and alloy catalyst through the preparation method provided, and can be used for the catalytic oxygen reduction reaction of PEMFC. The catalyst has high corrosion resistance, uniform particle distribution size, high specific surface area, and higher performance and stability than commercial platinum-carbon catalysts.
[0044] The invention is further described below by means of specific examples.
[0045] Example 1 In the embodiment of the present application, the platinum-containing precursor solution is prepared by adding H2PtCl6∙6H2O to deionized water.
[0046] The preparation method of the graphitized carbon-supported platinum-based catalyst of Example 1 of the present application comprises the following steps: KB600 was graphitized by ultrafast heating treatment at 1800℃ for 50s to obtain graphitized solid carbon material. Platinum nanoparticles were then loaded by impregnation method, and the carbon material after ultrafast heating treatment, platinum-containing precursor solution, and deionized water were prepared into a slurry with a platinum loading of 40 wt%. After drying, the product was transferred to a quartz boat and placed in a tube furnace. It was annealed in an argon-hydrogen mixed atmosphere at 300℃. The product was cooled and taken out, dispersed in a 0.5mol / L H2SO4 solution, magnetically stirred for 1h at a stirring speed of 400 rpm, and then the mixed solution was washed with deionized water under suction filtration. Finally, it was dried overnight at 65℃ under vacuum conditions to obtain a platinum-based catalyst uniformly loaded on the graphitized carbon layer.
[0047] Among them, the TEM images of KB600 before and after ultrafast heating treatment are as follows: Figure 1 As shown, Figure 1In the figure, a is the initial carbon material, and b is the graphitized carbon material after ultrafast heating treatment. It can be found that after ultrafast heating treatment, some graphitization occurs, but no continuous graphite structure is formed. The graphitization degree is about 18.24%. The carbon material after ultrafast heating treatment is subjected to BET and Raman tests. The test results are as follows: Figure 2 and Figure 3 The results show that the carbon material has a high specific surface area, a high degree of graphitization and retains a large number of lattice defects. At the same time, the platinum-based catalyst prepared in Example 1 was tested by XRD and TEM. The test results are as follows: Figure 4 and Figure 5 As shown, obvious platinum particle-related diffraction peaks were observed, and the nanoparticles were between 2-3 nm. The graphitized carbon obtained by the conventional heating method of annealing at 1800°C for 1 hour under argon and then cooling naturally was loaded with platinum nanoparticles by the same impregnation method as in Example 1. The TEM image of the catalyst obtained is as follows Figure 6 As shown, obvious agglomeration can be observed.
[0048] Example 2 The raw materials and preparation method of the graphitized carbon-supported platinum-based catalyst of Example 2 are substantially the same as those of Example 1, except that the annealing temperature is 400° C. The platinum-based catalyst prepared in Example 2 was subjected to XRD and TEM tests, and the test results are shown in FIG. Figure 4 and Figure 7 As shown, obvious diffraction peaks related to platinum particles were observed, and the nanoparticles were between 2-3 nm.
[0049] Example 3 In the embodiments of the present application, the platinum-containing precursor solution is prepared by adding H2PtCl6∙6H2O to deionized water, and the gold-containing precursor solution is prepared by adding chloroauric acid to deionized water.
[0050] The raw materials and preparation method of the graphitized carbon-supported platinum-based catalyst of Example 3 are basically the same as those of Example 1, except that the carbon material after ultrafast heating treatment, the platinum-containing precursor solution, the gold-containing precursor solution, and deionized water are prepared into a slurry with a total metal loading of 40wt%, wherein the Au content accounts for 5% of the total metal atomic ratio. The platinum-based catalyst prepared in Example 3 was subjected to XRD and TEM tests, and the test results are as follows: Figure 4 and Figure 8 As shown, obvious diffraction peaks related to platinum particles or platinum-gold alloys were observed, and the nanoparticles were between 2-3 nm.
[0051] Example 4 The raw materials and preparation method of the graphitized carbon-supported platinum-based catalyst of Example 4 are basically the same as those of Example 3, except that the annealing temperature is 400° C. The platinum-based catalyst prepared in Example 4 was subjected to XRD and TEM tests. The test results are as follows: Figure 4 and Fig. 9 As shown, obvious platinum particles or platinum-related diffraction peaks were observed, and the nanoparticles were between 2 and 3 nm.
[0052] Comparative Example A commercial Pt / C catalyst with a platinum loading of 40 wt% was used as a comparative example, where the loading was 20.0 μg Pt / cm 2 .
[0053] Performance Testing (1) Activity tests were performed on the Pt / C electrocatalysts prepared in Examples 1 and 2 and the Pt-M / C (M=Au) electrocatalysts prepared in Examples 3 and 4: During the activity test, the working electrode used a ring-disk electrode purchased from PINE, which was made of glassy carbon. When used, the graphitized carbon-supported platinum-based catalysts of Examples 1-4 and the comparative examples were respectively prepared into ink drops and applied to the surface of the disk electrode. After drying to form a flat catalytic layer, the activity test was performed. Platinum wire was usually used as the counter electrode, and a reversible hydrogen electrode (RHE) was used as the reference electrode.
[0054] Ink preparation process: 5 mg of the catalyst of Examples 1-4 or the comparative example was placed in a 20 mL sample bottle, 4.5 mL of formic acid and 500 μL of water were added, and then 15 μL of 5 wt% Nafion solution was added, and ultrasonic dispersion was performed uniformly.
[0055] Disk electrode drop coating process: The disk electrode area is 0.196 cm 2 Therefore, a total of 10 μL of ink was added to ensure that the catalyst loading of the embodiment or comparative example was 20 μg Pt / cm 2 .
[0056] Specific steps of the activity test process: After the three electrodes were connected to the CHI 760D / 760E electrochemical workstation, argon was introduced for at least 20 min to saturate the electrolyte with argon. Scan between 0.08 and 1.0 V vs. RHE at a rate of 500 mV / s in the saturated argon electrolyte until a stable CV curve was obtained. Scan between 0.08 and 1.0 V vs. RHE at a rate of 20 mV / s to obtain a CV curve for background correction. Then, oxygen was introduced for 20 min to remove argon, and then scan between 0.08 and 1.0 V vs. RHE at a rate of 20 mV / s at a speed of 1600 rpm, and then the ORR polarization curve was recorded.
[0057] The activities of the graphitized carbon-supported platinum-based catalysts prepared in Examples 1-4 and the commercial Pt / C catalysts of the comparative example were tested and compared in turn by this method. The activity test results are shown in FIG. Fig.10 As shown, Fig.10 In the figure, a is a polarization curve comparison diagram of the graphitized carbon-supported Pt / C electrocatalyst annealed at 300°C in an argon-hydrogen mixed atmosphere and a 40 wt% commercial Pt / C catalyst in Example 1, b is a polarization curve comparison diagram of the graphitized carbon-supported Pt / C electrocatalyst annealed at 400°C in an argon-hydrogen mixed atmosphere and a 40 wt% commercial Pt / C catalyst in Example 2, c is a polarization curve comparison diagram of the graphitized carbon-supported Pt-M / C (M=Au) electrocatalyst annealed at 300°C in an argon-hydrogen mixed atmosphere and a 40 wt% commercial Pt / C catalyst in Example 3, and d is a polarization curve comparison diagram of the graphitized carbon-supported Pt-M / C (M=Au) electrocatalyst annealed at 400°C in an argon-hydrogen mixed atmosphere and a 40 wt% commercial Pt / C catalyst in Example 4. Among them, the half-wave potential of the Pt / C electrocatalyst annealed at 300°C and 400°C in Examples 1 and 2, respectively, reached 0.9 V and 0.899 V, and the half-wave potential of the Pt-M / C (M=Au / Co / Ni / Fe) electrocatalyst annealed at 300°C and 400°C in Examples 3 and 4, respectively, reached 0.974 V and 0.907 V, which are much higher than the half-wave potential of 0.8V of the 40 wt% commercial Pt / C catalyst, and the mass activity of 0.9 V was increased to more than 1.2-2 times that of the 40 wt% commercial Pt / C catalyst. By observing and comparing the results, it is found that the platinum-based catalyst prepared in the examples of the present application has a significant activity advantage.
[0058] (2) Stability test of the Pt / C electrocatalyst prepared in Example 2: The stability test process is: first perform an initial activity test, then perform an accelerated cyclic voltammetry test, the condition is in a saturated argon electrolyte at a rate of 100 mV / s, the potential is scanned between 0.6 and 0.8 V vs. RHE for 120,000 times, the initial polarization curve (initial ORR) of the Pt / C electrocatalyst of Example 2, and the polarization curve after 10,000 cycles (after 10k CV) to 120,000 cycles (after 120k CV) are as follows: Fig.11 As shown, the activity test bar graph results before and after accelerated cycling are as follows Fig.12 As shown, the mass activity corresponding to the potential of 0.90 V decays by only 30%, reflecting excellent stability.
[0059] Through performance testing, it can be found that the graphitized carbon-loaded platinum-based catalyst prepared in the embodiment of the present application has good activity and stability, and has higher performance and stability than commercial platinum-carbon catalysts.
[0060] Through the preparation method provided in the present application, the non-graphitized solid carbon material is ultrafast heated to improve the degree of graphitization. At the same time, the retained rich defect sites can interact with the platinum or platinum alloy nanoparticles (or other metal nanoparticles) on the surface to play the role of anchoring the metal, so that the metal nanoparticles are better dispersed on the surface and are not easy to agglomerate, thereby effectively improving the catalytic activity.
[0061] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.
Claims
1. A method for preparing a graphitized carbon-supported platinum-based catalyst, characterized in that: The following steps are involved: The non-graphitized solid carbon material is subjected to ultra-fast heating treatment for graphitization to obtain a graphitized solid carbon material; Loading platinum-based nanoparticles on the graphitized solid carbon material by an impregnation method to obtain the graphitized carbon-loaded platinum-based catalyst; The ultrafast heating treatment is carried out under the conditions of 1200-3000° C. for 0.05-500 s.
2. The method for preparing a graphitized carbon-supported platinum-based catalyst according to claim 1, characterized in that: The step of loading platinum-based nanoparticles on the graphitized solid carbon material by an impregnation method comprises: The platinum-containing precursor solution, deionized water and the graphitized solid carbon material are prepared into a slurry with a platinum-based nanoparticle loading of 1-80 wt %, and dried to obtain a mixture; The mixture was transferred to a quartz boat and placed in a tube furnace, annealed in a reducing inert mixed atmosphere, taken out after cooling and dispersed in a 0.5 mol / L sulfuric acid solution, and magnetically stirred for 1-2 hours to obtain a mixed solution at a stirring speed of 200-600 rpm; The mixed solution was filtered and washed with deionized water, and dried at 70-100° C. overnight under vacuum conditions.
3. The method for preparing a graphitized carbon-supported platinum-based catalyst according to claim 2, characterized in that: The annealing temperature is 300-600° C., and the annealing time is 0.1-10 h.
4. The method for preparing a graphitized carbon-supported platinum-based catalyst according to claim 2, characterized in that: The platinum-based nanoparticles are one of platinum nanoparticles or platinum-based alloy nanoparticles, the platinum-based alloy nanoparticles are alloy nanoparticles of platinum and metal M, and the metal M is one or more of gold, cobalt, nickel, iron or ruthenium; The platinum-containing precursor solution is a platinum precursor solution, or the platinum-containing precursor solution includes a platinum precursor solution and a metal M precursor solution, and the content of the metal M accounts for 1-50% of the total metal atoms.
5. The method for preparing a graphitized carbon-supported platinum-based catalyst according to claim 4, characterized in that: The platinum precursor is one or more of H2PtCl6∙6H2O, K2PtCl6, Na2PtCl6, Na2PtCl4, K2PtCl4, Pt(NH3)4Cl2, Pt(NH3)2(NO2)2, and Pt(NO3)2.
6. The method for preparing a graphitized carbon-supported platinum-based catalyst according to claim 4, characterized in that: The metal M precursor is one or more of chloroauric acid, cobalt chloride, cobalt nitrate, cobalt sulfate, cobalt acetate, cobalt acetylacetonate, nickel nitrate, ruthenium chloride, ferric chloride, and ferric nitrate.
7. The method for preparing a graphitized carbon-supported platinum-based catalyst according to claim 2, characterized in that: The platinum-based nanoparticle loading is 5-60wt%.
8. The method for preparing a graphitized carbon-supported platinum-based catalyst according to claim 2, characterized in that: The reducing inert mixed atmosphere is an argon-hydrogen mixed atmosphere, and the hydrogen content in the argon-hydrogen mixed atmosphere is 1-20%.
9. The method for preparing a graphitized carbon-supported platinum-based catalyst according to claim 1, characterized in that: The non-graphitized solid carbon material is one or more of Vulcan XC72, KB300, KB600, BP2000 and Toray carbon.
10. A graphitized carbon-supported platinum-based catalyst, characterized in that: The catalyst is prepared by the method for preparing a graphitized carbon-supported platinum-based catalyst as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Fuel cell catalyst graphitized carbon carrier, preparation method thereof and fuel cell catalyst employing graphitized carbon carrier
CN108649243A
Preparation method of platinum-based synergistic catalyst with structure coupling effect
CN114497585A
High-specific-surface-area graphitized carbon carrier and preparation method thereof
CN117886314A
High surface area graphitized carbon and processes for making same
US20090208780A1
Cited By
Fuel cell catalyst and preparation method thereof
CN121260824A
Platinum-iron catalyst, preparation method thereof, membrane electrode and fuel cell
CN121307051A